Psychosemantic tools of self-assessing individual reflectivity - Savchenko, Olena; Савченко, Олена (Lesya Ukrainka Eastern European National University, 2019)
In this article, reflectivity is considered as an individual general ability to develop different attitudes to life events in order to reduce an external and internal uncertainty in situations. The objective of the research is to examine the self-assessment criteria for reflectivity with psychosemantic procedure. The author designs a modified version of the Ch. Osgood’s (1957) Semantic Differential (SD) for examining the content and formal features of the self-assessment criteria of reflectivity. This study suggests two main processes of self-assessment of reflectivity, notably differentiation and integration. The results of factor analysis indicate that individuals with high reflectivity level are aligned with low differentiation of the semantic space and monolithic nature of self-assessment criteria. The coherence and consistency of self-assessment criteria reduce the individuals’ level of inner uncertainty, transform external problems to familiar tasks and increase an efficient decision-making. A high level of differentiation is related to individual readiness to make a correct decision in the situation of multiple choice. High differentiation increases the individual adjustment and prevents from poor effects of high reflectivity. Consequently, a high level of reflectivity is associated with a low level of differentiation of self-assessment criteria.У статті рефлексивність розглядається як загальна здатність особистості ставати у різні позиції щодо подій власної життєдіяльності задля зниження ступеня зовнішньої та внутрішньої невизначеності. Мета дослідження – випрацювання оцінних критеріїв рефлективності на основі методів психосемантики. Автор розробила процедуру часткового семантичного диференціала, придатного для оцінки змісту і формальних рис рефлективності. Застосування факторного аналізу дало змогу виокремити лише дві узагальнені вторинні характеристики формальних ознак: рівень інтегрованості та диференціації. Виявлено, що високий рівень рефлексивності пов’язаний з низькою артикульованістю семантичного простору, з вираженою монолітністю оцінних критеріїв. Узгодженість та несуперечливість оцінних критеріїв допомагає суб’єктам знижувати рівень внутрішньої невизначеності, зводити зовнішні проблеми до типових задач. Висока артикульованість семантичного простору корелює з готовністю особи до перевірки висунутих припущень у ситуації множинного вибору, з домінуванням установки на правильність прийняття рішення. У результаті, встановлено, що високий рівень рефлексивності пов’язаний із низьким рівнем диференціації критеріїв оцінювання рефлексивної активності.
Психосемантичні засоби дослідження рефлексивної активності
Keywords: reflectivity; integration; differentiation; semantic space; psychosemantic tools; рефлексивність; інтеграція; диференціація; семантичний простір; психосемантичні засоби